Self-reported secondhand smoke exposure following the adoption of a national smoke-free policy in Poland: analysis of serial, cross-sectional, representative surveys, 2009–2019 - Mateusz Jankowski; Vaughan Rees; Wojciech Stefan Zgliczyński; Dorota Kaleta; Mariusz Gujski; Jarosław Pinkas (BMJ Open)
Objective We assessed changes in secondhand smoke (SHS) exposure in workplaces and public venues in Poland over a 9-year period following the adoption of a smoke-free policy in Poland in 2010.Design Six waves of cross-sectional surveys were carried out between 2009 and 2019.Participants A nationally representative sample of adult Polish residents (age 15 years and older) was surveyed.Survey respondents self-reported SHS exposure in the workplace and 12 different public venues. Data were analysed separately for samples consisting of (1) all respondents and (2) non-smokers only.SHS exposure was defined based on self-report, which may invoke error such as demand bias or recall bias and study protocol do not include participation of paediatric populations that are key limitations of this study.Results Within a year of adopting the smoke-free policy in 2010, the proportion of non-smokers exposed to SHS in Polish workplaces decreased by more than half (from 19.2% in 2009 to 9.5% in 2011). Over 10 years, a substantial reduction in SHS exposure was observed in all public venues. The highest decrease in SHS exposure was observed in transport services (decreased from 45.7% to 11.7% among all respondents and from 44.2% to 11.7% among non-smokers) and in bars/pubs (SHS exposure decreased from 45.0% to 7.0% among all respondents and from 39.4% to 7.0% among non-smokers).Conclusions This study demonstrates the substantial success of a national smoke-free law. Nevertheless, smoke-free laws must continue to be refined in terms of their legal boundaries as well as implementation strategies to eliminate disparities in SHS exposure in certain types of venues.